PENGENALAN OPTICAL AMPLIFIER DI DALAM SISTEM KOMUNIKASI OPTIK - Sunarto, Sunarto (Jurnal Teknik Elektro, 2005)
Attenuation in an Optical Communication Link always causes the transmitted signal powerbecome as lower as the length of the fiber become longer. For a long distancecommunication link like submarine cable needs a repeater to amplify the optical signalpower that transmitted in the fiber. The most popular repeater in long distancecommunication link is Optical Repeater with its Optical Amplifier. This paper is anintroduction of an Optical Amplifier. The most important part of an optical amplifier is theActive Medium. The active medium of an amplifier normally consist of 10 to 30 m length ofoptical fiber that has been slightly doped (e.g., 1000 ppm weight) with a rare earth elementsuch as erbium (Er) for 1550 nm wavelength and Praseodymium (Pd) for 1300 nmwavelength, and the host fiber material can be either standard silica, fluorite-based glass ormulti-component glass. The optical amplifier that consists of fiber doped with Erbium iscalled EDFA (ERBIUM DOPED FIBER AMPLIFIER). The simplified energy levelconcept of an EDFA and its basic operation how the photon signal could be amplified whencome through the active medium is simply introduced. Besides, the basic architecture of anEDFA, three configurations of the pumping direction of pump laser into the active mediumand the amplifier gain of an ADFA are also described.Keywords: Optical repeater, active medium, EDFA (erbium doped fiber amplifier)1. Pendahuluan